(3Ydefj GdaTds (3cJGHs - (3GdSgdj, Ydj Hf MSfs ([(3ecGf GdfTQ ZjQ eYQha(B]s (3GdafGQs, 2024)
(3GdaTd (B.. (3gh GdaQUI GdJj JJjM dc GdHOA ef LOjO HPcGA CcHQ (B. . (3TckQG dc CjgG GdaTd GdPj UfYJ ef GdfLGM hdhdG CfJ CjgG GdaTd deG hUdJ Edi eG hUdJ Edjg ef fLGMs
(3EgOGA ef eLdS GdfhGHs
Keywords: (3GdaTds; (3GdfLGMs; (3JOejQ GdPGJs